Frequency and accuracy of intraoperative bone margin sampling for T4a cancers of the head and neck at the QEII Health Sciences Centre: a retrospective chart review - Anna-Claire Lamport; Colin A. MacKay; Martin J. Bullock; S. Mark Taylor; Jonathan R. Trites; Martin Corsten; Matthew H. Rigby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Stage T4a cancers are associated with a 5-year survival of 21.6–59.0%. Adequate resection of these tumors is a critical factor in maximizing survival. Tumors invading bone pose a unique challenge to intraoperative bone margin assessment. Due to processing limitations, there had been no formal standardized protocol for intraoperative bone sampling at the QEII Health Sciences Centre. These resections often involve extensive reconstruction, making salvage surgery difficult if positive margins are detected post-surgically. The purpose of this study was to assess the accuracy and frequency of intraoperative bone margin assessment during the study period and to determine survival and recurrence rates associated with positive final bone margins. Methods A retrospective chart review was conducted including patients with stage T4a head and neck cancer involving bone that underwent primary surgical resection in Nova Scotia between 2009 and 2019. Eligible patients were identified through the Cancer Care Nova Scotia registry. Exclusion criteria included patients with stage T4a tumors involving bone that did not receive primary surgical treatment with curative intent and patients with stage T4a tumors that did not invade bone. Results Of 67 patients included, 50 were amenable to intraoperative bone margin sampling while 18 had intraoperative sampling. Four patients had positive intraoperative margins and one had final positive bone margins. The incidence of final bone margin positivity was 7.5%. Median survival following surgery was 4.56 years for patients with final negative bone margins (n = 62) and 3.98 years for patients with positive final bone margins (n = 5). All patients with final positive bone margins received adjuvant radiation therapy. Of patients with negative final bone margins, 16.1% received no adjuvant therapy, 61.3% received adjuvant radiation therapy and 21.0% received adjuvant chemoradiation therapy. Conclusion Intraoperative bone margin sampling occurred in 26.8% of all cases and 36.0% of amenable cases. Median survival of patients with positive final bone margins was 0.58 years lower than those with negative final bone margins, although this difference did not reach statistical significance. This will provide baseline data for comparison of the standardized intraoperative bone margin sampling protocol implemented at the QEII Health Sciences Centre. Graphical Abstract